Stonehenge - Allman, Toney (San Diego, CA : ReferencePoint Press, 2008)
An exploration of Stonehenge that discusses possible reasons it was built, how it may have been constructed, and who built the monument.
Mysterious Stonehenge -- The people of Stonehenge -- A culture of circles and rings -- Celts and Stonehenge -- Exploring the "why" of Stonehenge -- Stonehenge's destiny.
Includes bibliographical references (p. 86-88) and index.
Young Adult
Keywords: Megalithic monuments -- England -- Wiltshire -- Juvenile literature; Megalithic monuments -- England -- Wiltshire; Monuments -- Wiltshire (England); Stonehenge (England) -- Juvenile literature; Wiltshire (England) -- Antiquities -- Juvenile literature; Stonehenge (England); Wiltshire (England) -- Antiquities; Stonehenge (England); Wiltshire (England) -- Antiquities